Identification of Dynamics Modal Parameter for Car Chassis - M. M., Noor; M. S. M., Sani; M. M., Rahman; K., Kadirgama (IOP Publishing, 2011)
This paper explores and investigates the dynamic characteristics of car chassis structure by using experimental modal analysis (EMA) method and modal testing. Dynamic characteristics are divided into three parameters include natural frequency, damping factor and mode shape. In this study, modal testing was performed on the car chassis including the impact hammer and shaker test. Data analyzer was used to convert the response signal from the sensor, which was in the time domain to frequency domain. Result obtained from both methods, is compared on each axis (X, Y and Z axis). However, small discrepancy was observed in terms of natural frequency, which is within the range of 5%. Based on the results, interpretation and comparison were made for both methods.